Antimicrobial properties of Chlorocardium rodiei on Pseudomonas aeruginosa, Bacillus spp. and Candida albicans - DENNIS DAVID; RUTH DANIEL; DIANA SEECHARRAN (Smujo International, 2019)
Abstract. David D, Daniel R, Seecharran D, 2019. Antimicrobial properties of Chlorocardium rodiei on Pseudomonas aeruginosa, Bacillus spp. and Candida albicans. Nusantara Bioscience 11: 128-132. This research seeks to investigate the antimicrobial properties of Chlorocardium rodiei leaves and seeds on Pseudomonas aeruginosa, Bacillus spp. and Candida albicans. It also seeks to extract and identify the phytochemical compounds presented in leaves and seeds. The crude plant extract was obtained using the maceration method of extraction (ethanol and acetone as solvent) followed by rotary evaporation. Phytochemicals were analyzed from the crude extract using standard phytochemical procedures. 1%, 50% and 100% concentrations of each extract were prepared and used in the disk diffusion assay against C. albicans, P. aeruginosa, and Bacillus spp. and compared against Ciprofloxacin and Erythromycin for the bacteria and Fluconazole for the fungus. The results showed that the extract from the leaves possesses weak (?12 mm) to moderate (>12 ?15mm) inhibitory effect, while the extract from the seeds had weak (<12mm) inhibitory effect on the microorganisms. The phytochemical compounds tannins, essential oils, saponins, and phenols were tested positive from the crude extract. For the first time, the antimicrobial properties of C. rodiei’s leaves and seeds were evaluated and showed to possessed antimicrobial properties.